2023
DOI: 10.3390/ijerph20043767
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Consanguineous Marriage among Saudi Citizens of Albaha, a Cross-Sectional Study

Abstract: Consanguineous marriage (CM) is a prevalent kind of relationship in Muslim and Arab countries, and this type of relationship is linked to several health risks. This study was conducted to determine the prevalence of (CM), its associated hereditary diseases, and health-related issues among Saudi citizens in Albaha. This cross-sectional study was conducted between March 2021 to April 2021. Saudi citizens in Albaha who were aged ≥ 18 years and willing to participate were eligible for the study. A total of 1010 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A study conducted in Riyadh, Saudi Arabia, on a relatively small group of educated couples stated that 39.8% of CMs in their selected group ( 20 ). A recent cross-sectional study mentioned a 40% prevalence of CMs in Albaha province in KSA ( 21 ). They mentioned an astounding result: CM prevalence was higher among their study participants than their parents (40% vs. 31%).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Riyadh, Saudi Arabia, on a relatively small group of educated couples stated that 39.8% of CMs in their selected group ( 20 ). A recent cross-sectional study mentioned a 40% prevalence of CMs in Albaha province in KSA ( 21 ). They mentioned an astounding result: CM prevalence was higher among their study participants than their parents (40% vs. 31%).…”
Section: Discussionmentioning
confidence: 99%
“…This study highlighted that out of these marriages, first- and second-cousin unions constituted 72% and 28%, respectively. Notably, when comparing the prevalence of consanguineous marriages between the study participants and their parents, a lower rate was observed in the older generation (31%) as opposed to the participants (40%) [ 36 ].…”
Section: Reviewmentioning
confidence: 99%
“…As the prevalence of FCS and cancer-related mortality in the Saudi population appears to be increasing [6,7,[13][14][15][16][17][18], an understanding of which pathogenic variants (PVs) are prevalent in the Saudi population has practical value. As approximately 40% of all marriages in Saudi Arabia are between relatives [19,20], it is important to inform related individuals who wish to marry about the risk to future offspring of inheriting cancer-associated alleles from both parents. Moreover, knowing which variants in which genes contribute to the cancer incidence in Saudi populations would allow both for genetic screening and for physicians to recommend preventative measures, including surgical interventions or simply regular physical or radiological screening, to those at high risk due to inheritance of mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the field of medical genomics and, in particular in the use of next-generation sequencing (NGS), have opened new avenues for a better understanding of the underlying genetic risk factors for cancer [13][14][15][16][17][18][19][20][21]. NGS gene panels allow for the screening of multiple cancer-associated genes simultaneously, making them a cost-effective and time-saving way to detect familial variants [13,16].…”
Section: Introductionmentioning
confidence: 99%